Dmrt1 polymorphism and sex-chromosome differentiation in Rana temporaria - Rodrigues, Nicolas; Studer, Tania (Molecular ecology, 2017)
Sex-determination mechanisms vary both within and among populations of common frogs, opening opportunities to investigate the molecular pathways and ultimate causes shaping their evolution. We investigated the association between sex-chromosome differentiation (as assayed from microsatellites) and polymorphism at the candidate sex-determining gene Dmrt1 in two Alpine populations. Both populations harboured a diversity of X-linked and Y-linked Dmrt1 haplotypes. Some males had fixed male-specific alleles at all markers (“differentiated” Y chromosomes), others only at Dmrt1 (“proto-” Y chromosomes), while still others were genetically indistinguishable from females (undifferentiated X chromosomes). Besides these XX males, we also found rare XY females. The several Dmrt1 Y haplotypes differed in the probability of association with a differentiated Y chromosome, which we interpret as a result of differences in the masculinizing effects of alleles at the sex-determining locus. From our results, the polymorphism in sex-chromosome differentiation and its association with Dmrt1, previously inferred from Swedish populations, are not just idiosyncratic features of peripheral populations, but also characterize highly diverged populations in the central range. This implies that an apparently unstable pattern has been maintained over long evolutionary times.